Technology selection methods and applications in manufacturing: A review from 1990 to 2017. (December 2019) - Hamzeh, Reza; Xu, Xun
Graphical abstract: Highlights: Technology Selection state-of-the-art review paper. MADM approaches and technology selection methods. Application of technology selection methods in manufacturing industries. Abstract: In the recent decades several methods have been developed and applied for selecting the most preferable technologies with the aim of improving competitive advantage of companies. Considering this diversity, a decision-maker has an arduous job to find the most appropriate approach, and to justify the choice. This article performs a comprehensive review of commonly used Multi-Attribute Decision Making (MADM) methods for selecting technology in manufacturing industry. Using a systematic approach, authors collected and reviewed the papers addressing technology selection problem in this field. Selected articles then were classified according to the applied methods as well as the area of application. This paper provides a taxonomy of research works published during the last two decades, and identifies trends in the developments and application of these methods. Results of this research suggest that there has been a significant growth in utilization of MADM techniques for solving technology selection problems in manufacturing domain. It is also noted that several decision-support tools and methods have been developed and successfully applied in manufacturing industry druing this time period.